Rancang Bangun Sistem Informasi Pengelolaan Pemesanan Kamar Berbasis Website Pada Pabuaran Indah Guest House Purwokerto - Eveline Yunita; Mayasari Sasmito; Y Sukata (Media Aplikom, 2022)
Pabuaran Indah Guest House Purwokerto is one of hotel that needs a system. This hotel is in purwokerto since 12 august 2020. During the hotel room reservation process, they are still collaborating with online booking companies that make it possible to see other hotel references. In addition, the appearance of the hotel still needs to be improved in entering information, so there are shortcomings, namely in making hotel room reservation reports that are not in a system called Redpartner. So if you are going to make a report, the data from Redpartner will be copied back into Microsoft Excel so that there are often errors in calculations, wrong in entering room reservation data and takes time in making reports. Therefore, the information system needed to resolve the issues. The information will be contained in the system include among others: room data, room stock data, user data, payment data, order confirmation, room reservation report, cancel reservation report, and conversation Pabuaran Indah Guest House Purwokerto. System development method used is the System Development Life Cycle with waterfall. Pengujian models to determine how much and about the benefits of the system is to test the hypothesis and test the benefits.